Light-induced synthesis of silver nanoparticles using Ocimum tenuiflorum extract: Characterisation and application - Pandey V.K.; Upadhyay S.N.; Mishra P.K. (My University, 2025)
Stable silver nanoparticles of various sizes are synthesised using the aqueous extract of Tulsi (Ocimum tenuiflorum) as the reducing agent as well as a stabilising agent under the influence of light of wavelength ranging from 200 to 900 nm. The formation of silver nanoparticles is monitored using a UV-Visible spectrophotometer and the particle shape, size and stability are analysed using scanning electron microscopy, dynamic light scattering and zeta potential measurement techniques. It is observed that the size of the silver nanoparticles decreases on increasing the wavelength of irradiating light. The silver nanoparticles show antimicrobial activity against gram-positive (Bacillus subtilis), as well as gram-negative (Escherichia coli) bacteria. The antimicrobial activity shows an inverse relationship with the size of the silver nanoparticles. The bio-synthesised silver nanoparticles are successfully embedded in a polymeric film to act as an active antimicrobial film that can potentially release the active constituents. © The Author(s) 2020.